Minoli-Cordovana's authoritative computer & network security dictionary - Minoli, Daniel (Wiley-Interscience, 2006)
The dictionary is written for industry executives, managers, and planners who are charged with the responsibility of protecting their organizations from random, negligent, or planned attacks on their information technology resources. It not only defines terms, but also provides these professionals with critical insight into the terms' use and applicability in the field of IT security. Users can therefore refer to the dictionary as a handbook and guide to provide direction and support in all critical areas of computer and network security.